The Sleeping Beauty killer [compact disc, unabridged] - Clark, Mary Higgins; Burke, Alafair (Clark, Mary Higgins. Under suspicion novel, 2016)
Casey Carter was convicted of murdering her fiancé, famed philanthropist Hunter Raleigh III, fifteen years ago. And Casey claims, has always claimed, she's innocent. Although she was charged and served out her sentence in prison, she is still living 'under suspicion.' She hears whispers at the grocery store. She can't get a job. Even her own mother treats her like she's guilty. Her story attracts the attention of Laurie Moran and the Under Suspicion news team-it's Casey's last chance to finally clear her name, and Laurie pledges to exonerate her.